Using the Hands to Represent Objects in Space: Gesture as a Substrate for Signed Language Acquisition - Janke, Vikki; Marshall, Chloë R. (Frontiers in Psychology, 2017)
An ongoing issue of interest in second language research concerns what transfers from a speaker’s first language to their second. For learners of a sign language, gesture is a potential substrate for transfer. Our study provides a novel test of gestural production by eliciting silent gesture from novices in a controlled environment. We focus on spatial relationships, which in sign languages are represented in a very iconic way using the hands, and which one might therefore predict to be easy for adult learners to acquire. However, a previous study by Marshall and Morgan (2015) revealed that this was only partly the case: in a task that required them to express the relative locations of objects, hearing adult learners of British Sign Language (BSL) could represent objects’ locations and orientations correctly, but had difficulty selecting the correct handshapes to represent the objects themselves. If hearing adults are indeed drawing upon their gestural resources when learning sign languages, then their difficulties may have stemmed from their having in manual gesture only a limited repertoire of handshapes to draw upon, or, alternatively, from having too broad a repertoire. If the first hypothesis is correct, the challenge for learners is to extend their handshape repertoire, but if the second is correct, the challenge is instead to narrow down to the handshapes appropriate for that particular sign language. 30 sign-naïve hearing adults were tested on Marshall and Morgan’s task. All used some handshapes that were different from those used by native BSL signers and learners, and the set of handshapes used by the group as a whole was larger than that employed by native signers and learners. Our findings suggest that a key challenge then when learning to express locative relations might be reducing from a very large set of gestural resources, rather than supplementing a restricted one, in order to converge on the conventionalised classifier system that forms part of the grammar of the language being learned.